2019
DOI: 10.1080/1600910x.2019.1586741
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding recognition: an empirical-theoretical contribution to the concept

Abstract: The past decades have witnessed growing interest in the concept of recognition, in social movements as well as in social theory. While the 'recognition turn' has made recognition a cornerstone in social and political philosophy, empirical interestin sociology, anthropology and business studiesremains limited and has mainly focused on misrecognition and disrespect. As a result, recognition as a theoretical ideal remains largely divorced from the lived and messy realities of people's everyday search for recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…The same applies to the way the workplace is adjusted: structured tasks seem to make recognition for lower-skilled employees possible, but undermine the experiences of competency and craftsmanship of the more skilled employees. The recognition of one comes with the misrecognition of the other (see also Sebrechts, Tonkens, and Da Roit 2019).…”
Section: Fragility and Limits Of Recognitionmentioning
confidence: 99%
“…The same applies to the way the workplace is adjusted: structured tasks seem to make recognition for lower-skilled employees possible, but undermine the experiences of competency and craftsmanship of the more skilled employees. The recognition of one comes with the misrecognition of the other (see also Sebrechts, Tonkens, and Da Roit 2019).…”
Section: Fragility and Limits Of Recognitionmentioning
confidence: 99%
“…. ok, but I gave like 100%.’ For Kasia, this was an instance where recognition and misrecognition of a worker’s performance are ‘enfolded’ (Sebrechts et al, 2019: 173).…”
Section: Resultsmentioning
confidence: 99%
“…In this light, Honneth’s (1996) theory of recognition, wherein intersubjective recognition forms the foundation of practical identity, has inspired a recent ‘recognition turn’ in mainstream sociological (Boston, 2018; May, 2016; Sebrechts et al, 2019) and organisational literature (Dashtipour and Vidaillet, 2017; Hancock, 2016). Referring to the positive affirmation of others as human agents, Honnetian recognition is actualised through purposive action and communication that another individual has value: first, as an individual with basic rights, but also as an individual with specific abilities, goals and achievements (Honneth, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, critical engaged research will be useful for exploring how recognition effects of voice across both paradigms interact with each other. Research has shown that experiences of misrecognition can be enfolded within experiences of recognition (Sebrechts, Tonkens and Roit, 2019). This prompts future research into how proactive approaches to voice which seek to support and maintain workers' connections with their loved ones and communities (i.e.…”
Section: Discussionmentioning
confidence: 99%